(untitled) (Global Journal of Human-Social Science, 2016)
This work examined the impediments corruption pose on Nigerias economy It states that Corruption in Nigeria is endemic in all facets and it has continued to challenge the goals of sustainability of development efforts in all ramifications Thus this chapter provides explanations on the corruption variable in the country its negative impacts consequences and impediments towards the country march to economic recovery in post 2015 and the sustenance of development effort The work applied the historical method of data collection secondary sources using descriptive mechanism of analysis